BUN as an Independent Predictor of Post-Hospital-Discharge Mortality among Older Veterans - Sullivan, Dennis H.; Sullivan, S.C.; Bopp, M.M.; Roberson, P.K.; Lensing, S.Y. (The Journal of nutrition, health & aging, 2018)
An elevated blood urea nitrogen (BUN) in known to be an important prognostic indicator in patients with end-stage heart or kidney disease or certain other life-threatening illnesses. However, it is less certain as to whether an elevated BUN is an independent predictor of long-term mortality risk in less seriously ill patients. To address this issue, we examined the relationship between BUN and long-term mortality after adjusting for potential confounders and other indicators of health status/disease severity, in a select population of older medically stable Veterans. Long-term prospective cohort study. Outpatient follow-up of patients discharged from a recuperative care and rehabilitation unit (RCRU) of a Department of Veterans Affairs Community Living Center. 383 older Veterans (mean age = 78.6Â±7.6 years, 98% male, and 87% white) discharged alive and in stable medical condition. At discharge, each subject completed a comprehensive assessment and was then monitored as an outpatient for up to 9.3 years. Associations between blood urea nitrogen at RCRU discharge and mortality were identified utilizing Cox proportional hazards (PH) regression analyses adjusting for conditions known to confound this relationship. Within the follow-up period, 255 subjects (67%) died. In the unadjusted Cox PH model, a BUN > 30 mg/dL was associated with a nearly 2-fold increased risk of mortality (hazard ratio 1.90, 95%CI 1.41 - 2.56). The association between BUN and long-term mortality remained highly significant after adjusting for potential confounders (hazard ratio 1.78, 95%CI 1.29 - 2.44). Our findings support BUN levels as an independent predictor of long-term mortality in older, medically stable Veterans. An elevated BUN may be reflective of global health status rather than solely an indicator of the severity of acute illness or unstable chronic disease.